ACCELERATED TOOTH MOVEMENT USING PLASMA RICH PROTEIN-A CRITICAL REVIEW - Idaayath, Azmina; Srinivasan, Dilip; Kalidass, Priya; Chakravathy, Sushil; Rajaram, Krishnaraj; Kannan, Ravi (International Journal of Psychosocial Rehabilitation, 2020)
The accessibility of orthodontic treatment has increased the number of patients opting for the treatment. Orthodontic treatment has shown to improve the overall well-being of the patient. Still, there are many disadvantages to orthodontic treatmentof which patient acceptability to prolonged orthodontic treatment is of primary concern. Many surgical and non-surgical methods have been developed and employed to hasten the treatment. Amongst various methods used this review article will highlight the use of protein rich plasma(PRP) as an adjunct to accelerate tooth movement, which acts by the changing the alveolar bone density due to the presence of osteoclast.